2013
DOI: 10.1002/2013wr014240
|View full text |Cite
|
Sign up to set email alerts
|

Mapping evapotranspiration trends using MODIS and SEBAL model in a data scarce and heterogeneous landscape in Eastern Africa

Abstract: [1] Evapotranspiration (ET) accounts for a substantial amount of the water use in river basins particular in the tropics and arid regions. However, accurate estimation still remains a challenge especially in large spatially heterogeneous and data scarce areas including the Upper Pangani River Basin in Eastern Africa. Using multitemporal Moderate-resolution Imaging Spectroradiometer (MODIS) and Surface Energy Balance Algorithm of Land (SEBAL) model, 138 images were analyzed at 250 m, 8 day scales to estimate ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 70 publications
(87 reference statements)
3
51
0
Order By: Relevance
“…Overall, the uncertainty on the mean annual ET, as calculated by us on the land cover level, is less than 12%. This is comparable with the results of Kiptala et al [60] who used SEBAL data in the Upper Pangani River Basin (Kenya/Tanzania) and other published validation results [11].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Overall, the uncertainty on the mean annual ET, as calculated by us on the land cover level, is less than 12%. This is comparable with the results of Kiptala et al [60] who used SEBAL data in the Upper Pangani River Basin (Kenya/Tanzania) and other published validation results [11].…”
Section: Discussionsupporting
confidence: 91%
“…The 95% confidence interval for basin mean annual SSEBop ET estimates is 39 mm/yr, which is comparable with 42 mm/yr using the GFET dataset. Overall, uncertainties in the mean annual ET from this study are similar with the reported uncertainties in Kiptala et al [60] using SEBAL in the Upper Pangani River Basin (Kenya/Tanzania) and with other published validation results [11]. This indicates the reliability of the ET estimates derived in this study for various hydrological applications.…”
Section: The Assessment Of the Uncertainties On The Et Estimatessupporting
confidence: 89%
See 2 more Smart Citations
“…The Terra earth observation system was launched in the year 1999 and the Aqua earth observation system in the year 2002 [50]. The Terra satellite goes from north to south across the equator and Aqua passes south to north over the equator [3].…”
Section: Modis Et Data and Pre-processingmentioning
confidence: 99%